(untitled) (Clinics, 2021)
This study aimed to compare the effectiveness of 0.12% chlorhexidine alone and 0.12% chlorhexidine in combination with toothbrushing to prevent ventilator-associated pneumonia (VAP) in mechanically ventilated patients. The Embase, Latin American and Caribbean Health Science Literature, PubMed, Scientific Electronic Library Online, Scopus, LIVIVO, Web of Science, Cochrane Library, OpenThesis, and Open Access Thesis and Dissertations databases were used. Only randomized controlled trials without restrictions on the year or language of publication were included. Two reviewers assessed the risk of bias using the Joanna Briggs Institute Critical Appraisal Tool. A meta-analysis using a random-effects model estimated the combined relative risk (RR). The Grading of Recommendations, Assessment, Development and Evaluations approach was used to assess the certainty of the evidence. Initially, 2,337 studies were identified, of which 4 were considered in the systematic review and 3 in the meta-analysis (total sample: 796 patients). The studies were published between 2009 and 2017. All eligible studies had a low risk of bias. The meta-analysis revealed that the risk of VAP was 24% lower in patients receiving chlorhexidine combined with toothbrushing than in those receiving chlorhexidine alone (RR: 0.76; 95% confidence interval: 0.55-1.06), with moderate certainty of evidence and without statistical significance. In conclusion, considering the limitations of this study, a standard protocol for the prevention of VAP is not yet recommended. More studies with larger sample sizes are needed to draw strong conclusions. However, considering that toothbrushing is a simple intervention, it should be a common practice in mechanically ventilated patients, especially among patients with coronavirus disease.